Geoquímica de perfis lateríticos na chapada sedimentar do Triângulo Mineiro - Amendola, Danilo de Paulo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The ferruginous sandstone (Serra da Galga member) from Marilia formation present in sedimentary mining triangle plateaus - MG (southeast Brazil) is still not properly characterized, as well as the presence of a rich layer Fe nodules which is not properly understood, as are the alteration products of this material that may be linked to the presence of refractory clays which are characterized by intimate relationship between Fe and Al. Aluminum is widely present on top of these plateaus. This course conclusion paper characterized the mineralogy and distribution of smaller elements both rust sandstone evolved as soil above this sandstone. The characterization has been done by using X-ray fluorescence techniques (XRF), the iron was removed by using the CBD method (dithionito-citratebicarbonate), and X-ray diffraction (XRD) and analysis of the products extracted by the CBD method by ICP- OES were made to characterize the material. The results of the XRF show great variation of Al and Si, Fe with almost constant behavior in the average depth of 110 cm, where it has the highest concentration levels. Fe appear associated with the V and Ce. CDB results show a clear relation of Fe with Al. Al does not have in this case compared with Cr or any other item. The concentration of extracted Al was always below the concentration of Fe. In the region, the formation of this Latosols- Gleysols system is subject to topography and its influence on local water regime, a regime that has direct influence on the formation of supergene accumulations as in the area and results in aluminum accumulation in refractory clays exploited by IBAR mining

O arenito ferruginoso (membro Serra da Galga) da Fm. Marilia presente nas chapadas sedimentares do triângulo mineiro - MG, ainda não é devidamente caracterizado, assim como a presença de uma camada rica em nódulos de Fe que também não é devidamente compreendida, assim como os produtos de alteração desse material que podem estar ligados à presença das argilas refratárias que se caracterizam pela intima relação entre o Fe e o Al, alumínio que está amplamente presente no topo dessas chapadas. Este trabalho caracterizou a mineralogia e a distribuição dos elementos menores tanto do arenito ferruginoso quanto do solo evoluído acima deste arenito. A caracterização foi feita utilizando-se técnicas de fluorescência de raios X (FRX), desferrugenização do material empregando o método CDB (dithionito-citrato-bicarbonato), difração de raios X (DRX) e análise dos produtos extraídos pelo método CDB por ICP-OES. Os resultados da FRX evidenciam grande variação do Al e da Si, com Fe quase sempre constante no perfil salvo na profundidade média de 110 cm, onde ele apresenta níveis de máxima concentração. Associados ao Fe aparecem o V e Ce. Os resultados do CDB mostram uma clara relação do Fe com o Al. O Al não possui nesse caso relação com Cr ou quaisquer outros elementos. A concentração de Al extraída foi sempre abaixo da concentração do Fe. Pode-se concluir que na região, a formação desse sistema Latossolos - Gleissolos está condicionada a topografia e sua influência no regime de águas do local, regime que tem influência direta na formação das acumulações supérgenas como acontece na área e resulta no acumulo de alumínio nas argilas refratárias exploradas pela mineradora IBAR
Keywords: Geoquimica; Geologia; Arenito; Mineralogia; Triangulo Mineiro (MG)